The ferns and fern-allies of Ulu Endau, Johore, Malaysia - Kiew, Ruth; Parris, B. S.; Madhavan, S.; Edwares, P. J.; Wong, K. M. (Malaysian Nature Society, 1987)
81 fern species in 41 genera and 20 families, 8 selaginellas and 5 lycopods were collected from the ulu Endau area in Johore, Malaysia. Schizaea ftstulosa is a new record for Peninsular Malaysia. Several species which are usually montane species in Peninsular Malaysia were collected at about 700 m, viz. Gleichenia microphylla, Matonia pectinate, Trichomanes ridleyi, T. meifolium, Crypsinutrilobus,Schizaea ftstulosa and Lycopodium, carolinianum; Dipteris conjugata, usually montane but also recorded at sea level in Singapore, grows in the lowlands at ulu Endau, Several ferns are rheophytes, of which Dipteris lobbiana is the most conspicuous.